Contextually-Dependent Lexical Semantics - Verspoor, Cornelia M (University of Edinburgh. College of Science and Engineering. School of Informatics., 1997)
This thesis is an investigation of phenomena at the interface between syntax, semantics, and pragmatics, with the aim of arguing for a view of semantic interpretation as lexically driven yet contextually dependent. I examine regular, generative processes which operate over the lexicon to induce verbal sense shifts, and discuss the interaction of these processes with the linguistic or discourse context. I concentrate on phenomena where only an interaction between all three linguistic knowledge sources can explain the constraints on verb use: conventionalised lexical semantic knowledge constrains productive syntactic processes, while pragmatic reasoning is both constrained by and constrains the potential interpretations given to certain verbs. The phenomena which are closely examined are the behaviour of PP sentential modifiers (specifically dative and directional PPs) with respect to the lexical semantic representation of the verb phrases they modify, resultative constructions, and logical metonymy. The analysis is couched in terms of a lexical semantic representation drawing on Davis (1995), Jackendoff (1983, 1990), and Pustejovsky (1991, 1995) which aims to capture “linguistically relevant” components of meaning. The representation is shown to have utility for modeling of the interaction between the syntactic form of an utterance and its meaning. I introduce a formalisation of the representation within the framework of Head Driven Phrase Structure Grammar (Pollard and Sag 1994), and rely on the model of discourse coherence proposed by Lascarides and Asher (1992), Discourse in Commonsense Entailment. I furthermore discuss the implications of the contextual dependency of semantic interpretation for lexicon design and computational processing in Natural Language Understanding systems.
Institute for Communicating and Collaborative Systems
Keywords: syntax; semantics; pragmatics; semantic knowledge